2001
DOI: 10.1139/w01-108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hybrid biphenyl dioxygenases obtained by recombiningBurkholderiasp. strain LB400bphAwith the homologous gene ofComamonas testosteroniB-356

Abstract: The bacterial degradation of polychlorinated biphenyls depends on the ability of the enzyme biphenyl 2,3-dioxygenase (BPDO) to catalyze their oxygenation. Analysis of hybrid BPDOs obtained using common restriction sites to exchange large DNA fragments between LB400 bphA and B-356 bphA showed that the C-terminal portion of LB400 alpha subunit can withstand extensive structural modifications, and that these modifications can change the catalytic properties of the enzyme. On the other hand, exchanging the C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Plasmid pQE31[LB-400-bphAE], in which bphA was mutated to introduce an AvrII site at position 1354, was described previously (14); it encodes for a fused His-tagged ISP BPH (14,15) carrying the His tag on BphA. Plasmid pYH31[LB400-bphF-GBC] was described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pQE31[LB-400-bphAE], in which bphA was mutated to introduce an AvrII site at position 1354, was described previously (14); it encodes for a fused His-tagged ISP BPH (14,15) carrying the His tag on BphA. Plasmid pYH31[LB400-bphF-GBC] was described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on various biphenyl 2,3-dioxygenases have revealed considerable differences in their congener selectivity patterns, as well as their preference for the attacked ring (4,12,22,28,38,44).…”
mentioning
confidence: 99%
“…We note that these findings contrast those of Hurtubise et al (1998) and Chebrou et al (1999), who reported a significant contribution of the β subunit to BDO-substrate interaction. However, a recent publication from this group (Barriault et al, 2001) reported no major influence of the small subunit on substrate specificity. Based on all fusions generated, the α subunit may be divided into eight segments, designated A to H (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Although investigations of different ARHDOs are of limited comparability, we note that Beil et al (1998) and Parales et al (2000) reported effects of amino acid substitutions at five or two positions, respectively, within the corresponding regions of a toluene or a naphthalene dioxygenase, respectively. Barriault et al (2001), however, exchanging a region between BDOs of strains LB400 and B-356 that comprises the region substituted in BDO-H30, found only a minor influence on substrate specificity. These differences in results may be a consequence of the different assays used.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation